Environmental dust removal from inclined hydrophobic glass surface: avalanche influence on dynamics of dust particles. Issue 59 (2nd October 2018) - Yilbas, Bekir Sami; Al-Sharafi, Abdullah; Ali, Haider; Al-Aqeeli, Nasser; Al-Qahtani, Hussain; Al-Sulaiman, Fahad; Abu-Dheir, Numan; Abdelmagid, Ghassan; Elkhazraji, Ali
Abstract : The removal of environmental dust particles from optically transparent glass surfaces is considered, and the dynamics of the dust particles on the inclined hydrophobic glass surface is examined. Abstract : The removal of environmental dust particles from optically transparent glass surfaces is considered, and the dynamics of the dust particles on the inclined hydrophobic glass surface is examined. The glass surfaces are coated by functionalized nano-sized silica particles to create a hydrophobic wetting state on the surface. A thin layer of environmental dust particles, collected from the local area of Dammam in the Kingdom of Saudi Arabia (KSA), is deposited on the surface while mimicking the dust accumulation on the surfaces in the dusty days of KSA. In order to increase the removal rate of the dust particles from the inclined hydrophobic glass surfaces, high density particles, which are higher than the density of the dust particles, are locally distributed on the dust particle-deposited surface while generating the avalanche influence on the inclined surface. The motion of the dust and high density particles on the inclined surface is monitored using a high speed camera. The predictions of the dust particles' acceleration and velocity are compared to those obtained from the high speed camera data. It is found that the predictions of velocity and acceleration of the dust particles agree well with the experimental data. Local insertion of the high density particles generates avalanche influence on the inclined surface while initiating the removal of the dust particles from the hydrophobic surface at small inclination angles. The size of the area where the dust particles are removed from the inclined surface increases with enlarging coverage area of the high density particles. The dust-removed surface, under the avalanche influence, improves the UV-visible transmittance of the hydrophobic glass.